Asymmetric physiological response of a reef-building coral to pulsed versus continuous addition of inorganic nutrients - Rene M. van der Zande; Yannick R. Mulders; Dorothea Bender-Champ; Ove Hoegh-Guldberg; Sophie Dove (Scientific Reports, 2021)
Abstract Coral reefs, especially those located near-shore, are increasingly exposed to anthropogenic, eutrophic conditions that are often chronic. Yet, corals under unperturbed conditions may frequently receive natural and usually temporary nutrient supplementation through biological sources such as fishes. We compared physiological parameters indicative of long- and short-term coral health (day and night calcification, fragment surface area, productivity, energy reserves, and tissue stoichiometry) under continuous and temporary nutrient enrichment. The symbiotic coral Acropora intermedia was grown for 7 weeks under continuously elevated (press) levels of ammonium (14 µmol L−1) and phosphate (10 µmol L−1) as separate and combined treatments, to discern the individual and interactive nutrient effects. Another treatment exposed A. intermedia twice-daily to an ammonium and phosphate pulse of the same concentrations as the press treatments to simulate natural biotic supplementation. Press exposure to elevated ammonium or phosphate produced mixed effects on physiological responses, with little interaction between the nutrients in the combined treatment. Overall, corals under press exposure transitioned resources away from calcification. However, exposure to nutrient pulses often enhanced physiological responses. Our findings indicate that while continuous nutrient enrichment may pose a threat to coral health, episodic nutrient pulses that resemble natural nutrient supplementation may significantly benefit coral health and physiology.